2006
DOI: 10.1002/cne.21191
|View full text |Cite
|
Sign up to set email alerts
|

Selective enrichment of DJ‐1 protein in primate striatal neuronal processes: Implications for Parkinson's disease

Abstract: Mutations in DJ-1 cause autosomal recessive, early-onset Parkinson's disease (PD). The precise function and distribution of DJ-1 in the central nervous system remain unclear. In this study, we performed a comprehensive analysis of DJ-1 expression in human, monkey, and rat brains using antibodies that recognize distinct, evolutionarily conserved epitopes of DJ-1. We found that DJ-1 displays region-specific neuronal and glial labeling in human and non-human primate brain, sharply contrasting the primarily neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 68 publications
2
45
0
Order By: Relevance
“…Increased levels of p53 and phosphorylated p53 were found in the substantia nigra and striatum of the postmortem PD brains (34,35); DJ-1 is also selectively expressed within these two regions critically involved in PD pathogenesis (36,37). Interestingly, our study demonstrates that the protective effects of DJ-1 are not caused by the change of p53 levels but by inhibiting p53 transcriptional activities.…”
Section: Discussionmentioning
confidence: 54%
“…Increased levels of p53 and phosphorylated p53 were found in the substantia nigra and striatum of the postmortem PD brains (34,35); DJ-1 is also selectively expressed within these two regions critically involved in PD pathogenesis (36,37). Interestingly, our study demonstrates that the protective effects of DJ-1 are not caused by the change of p53 levels but by inhibiting p53 transcriptional activities.…”
Section: Discussionmentioning
confidence: 54%
“…Alternatively, different subsets of DJ-1-interacting proteins may be available in cells subjected to different insults, resulting in the formation of protein complexes with different functional outputs. Another unresolved question is whether the protective mechanisms of DJ-1 in our mixed cultures and in human brain are activated preferentially in neurons or glia, given that the protein is abundant in both cell types (Bandopadhyay et al 2004;Olzmann et al 2007). In this study, we showed via immunocytochemical staining that DJ-1-mediated upregulation of iHsp70 in MG132-treated cultures occurs in dopaminergic and non-dopaminergic neurons and in glia.…”
Section: Discussionmentioning
confidence: 69%
“…DJ-1 downregulation enhances cell death by OS, ER stress, and proteasome inhibition [234], while the localization of DJ-1 to mitochondria is associated with protective actions against some mitochondrial poisons [235]. Exogenously applied DJ-1 was shown to localize to mitochondria, the cytosol, nucleus, and microsomes [227,231,232], while endogenous DJ-1, locating to presynaptic terminals of striatal axons and dendrites [236], revealed interaction with membranes of cultured cells [237]. Furthermore, DJ-1 partly colocalizes with the synaptic marker Rab3A at synaptic terminals, which suggests interaction with membrane trafficking [238].…”
Section: The Role Of α-Synuclein Mutationsmentioning
confidence: 99%